Corporate social responsibility and loyalty: Intervening influence of customer satisfaction and trust - Muzammal Ilyas Sindhu; Muhammad Arif (Cogent Business & Management, 2017)
This study investigated the relationship between value relevance and ethical standards as determinants of commitment to corporate social responsibility (CSR) activities and customer loyalty with the intervening effect of customer satisfaction, corporate reputation, and trust. Multidimensional questionnaires were designed and the structural equation modeling was applied to investigate relationships. Our results provided a general picture of the theoretical process by which the sequential relationship between value relevance, ethical standards, commitment, trust, satisfaction, reputation, and loyalty. The commitment to CSR is positively influencing customer loyalty and customer satisfaction, trust, and corporate reputation also intervened in their relationships. This study is theoretical contributing as identified customer satisfaction, trust, and corporate reputation as intervening factors, while from the practical point of view, customer trust is important because it is considered as justification based on morality . It is, therefore, important that organizations should properly disseminate practical and moral information. This is a novel study in Pakistani context because it is a theoretical contribution in existing literature as well as in organizational CSR practices leading to customer satisfaction, trust, and loyalty.
Keywords: 650